ESTIMATING OF DEBT FINANCING, EQUITY FINANCING TOWARDS PROFIT EXPENSE IN INDONESIA (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
The main purpose of this empirical research was to examine whether a relationship exists between funding sources, which are debt financing and equity financing, and profit expense. A panel data regression model was carried out in this research on companies registered on Jakarta Islamic Index (JII) Indonesia during the period of 2015-2019. As many as 110 observation samples were collected through purposive sampling. The results of the current research discovered that equity financing affects the capital cost or profit expense positively and statistically significantly. Meanwhile, debt financing does not have a significant effect on profit expense. Specifically, such results indicate that debt financing does not affect profit expense. However, evidence was found that equity financing significantly affects profit expense, indicating that the equity financing system is more oriented towards working capital. Our research has provided empirical evidence that the higher the source of funding, namely equity financing, the higher the profit expense.